LEVEL OF ATTITUDE, MEDICATION ADHERENCE, AND QUALITY OF LIFE AMONG PATIENTS WITH TUBERCULOSIS - I Kadek Dwi Swarjana; Tintin Sukartini; Makhfudli Makhfudli (International Journal of Nursing and Health Services (IJNHS), 2019)
Tuberculosis (TB) is a global health concern worldwide. The study aimed to describe the level of attitude, medication adherence, and quality of life among patients with tuberculosis. The cross-sectional study design was applied in this study. Seventy samples were selected by using purposive sampling technique. The findings showed that most of the patients were a moderate level of attitude in medication adherence (45.7%). Regarding compliance with obedient, 61.4% of patients were non-compliance in medication. The majority of patients (64.3%) were a moderate level of quality of life; only 14.3% of patients have a high level of quality of life. The support and effective strategy need to improve the attitudes, adherence, and quality of life of patients with pulmonary TB. Keywords Pulmonary TB, attitude, compliance, quality of life, Supervision of medicine drug